Choice of the means of transport for the creation of a logistic system relying on uncertainties - Sokolova, Maria Leonidovna; Chernov, Vladimir Georgievich (Vojnotehnički glasnik / Military Technical Courier, 2016)
In this work, a variant of the method of the multicriteria alternative choice ELECTRE, which allows taking into account uncertainties of expert estimates, was developed and studied. The modified method ELECTRE was tested on a problem solution of the logistics management transportation system "point of departure – point of destination". The suggested approach can increase the effectiveness of logistic management of goods delivery transport systems and reduce delivery time.
Keywords: method ELECTRE; fuzzy sets; neural network; logistics; goods delivery